2010
DOI: 10.1159/000322320
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Vitamin A Insufficiency Results in Adverse Ventricular Remodeling after Experimental Myocardial Infarction

Abstract: Background/Aims: The role of tissue vitamin-A insufficiency on post-infarction ventricular remodeling is unknown. We tested the hypothesis that cardiac vitamin A insufficiency on post-infarction is associated with adverse myocardial remodeling. Methods: After infarction, rats were allocated into two groups: C (controls, n=25); VA (dietary vitamin A restriction, n= 26). After 3 months, the animals were submitted to echocardiogram, morphometric and biochemical analysis. Results: Rats fed the vitamin-A-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…These investigators further proposed that ATRA signaling may play a role in regulating damage and repair during heart remodeling (5). Minicucci et al (26) reported that local heart retinoid insufficiency is associated with intensified ventricular remodeling after experimental myocardial infarction, worsening diastolic dysfunction. These differences were accompanied by an increase in BNP expression.…”
Section: Levels In Bco1mentioning
confidence: 99%
“…These investigators further proposed that ATRA signaling may play a role in regulating damage and repair during heart remodeling (5). Minicucci et al (26) reported that local heart retinoid insufficiency is associated with intensified ventricular remodeling after experimental myocardial infarction, worsening diastolic dysfunction. These differences were accompanied by an increase in BNP expression.…”
Section: Levels In Bco1mentioning
confidence: 99%
“…Pressure values, maximum LV pressure decrease rate, and maximum LV pressure development rate were recorded. Procedures and measurements were performed according to a previously described method [22-24]. …”
Section: Methodsmentioning
confidence: 99%
“…Infarct size was calculated by dividing the endocardial and epicardial circumferences of the infarcted area by the total epicardial and endocardial ventricular circumferences. The measurements were performed on midventricular sections (5-6 mm from the apex) under the assumption that the left midventricular slice shows a close linear relation with the sum of the area measurements from all of the heart sections [25]. …”
Section: Methodsmentioning
confidence: 99%